Strain Relaxation of InAs Quantum Dots on Misoriented InAlAs(111) Metamorphic Substrates - Artur Tuktamyshev; Stefano Vichi; Federico Guido Cesura; Alexey Fedorov; Giuseppe Carminati; Davide Lambardi; Jacopo Pedrini; Elisa Vitiello; Fabio Pezzoli; Sergio Bietti; Stefano Sanguinetti (Nanomaterials, 2022)
We investigate in detail the role of strain relaxation and capping overgrowth in the self-assembly of InAs quantum dots by droplet epitaxy. InAs quantum dots were realized on an In<semantics>0.6</semantics>Al<semantics>0.4</semantics>As metamorphic buffer layer grown on a GaAs(111)A misoriented substrate. The comparison between the quantum electronic calculations of the optical transitions and the emission properties of the quantum dots highlights the presence of a strong quenching of the emission from larger quantum dots. Detailed analysis of the surface morphology during the capping procedure show the presence of a critical size over which the quantum dots are plastically relaxed.